A strategic approach to merging large corporations through the efficiency and effectiveness of their business in world practice - Sara Fuchs; Dino Baricevic; Marija Vukoja (UTMS Journal of Economics, 2022)
Developing a wide network of cooperative relationships is an important part of the strategic management process of successful companies. If a company wants to have excellent business results, it should create strategic alliances and thus use the potentials, resources, skills and strength of other companies in building its own business strategies. All sorts of changes in world business are creating a whole new context for the strategic behaviour of companies. There is an intensive trend of mergers and strategic connections of the world's largest companies. Integrations, strategic cooperation and connections have affected almost all world activities. Strategic alliances are one of the instruments for implementing development strategies. However, other available development versions must not be forgotten either. Cooperation makes sense with others only if it is designed as a means in which the company will create added value. It should not be forgotten that strategic alliances are a long-term investment that involves a risk: a lot of effort is required before satisfactory results are achieved. This must not discourage businesses, especially those wishing to keep up with global and regional competition.
Keywords: F01; Z32; 330; strategic management; integration; alliance; risk